Excellent Maid Service Agency / Dominic J. Omok ... [et al.] - Omok, Dominic J.; Mison, Fenzin Night Priscellah; Danil, Mardianie; Longfield, Dayang Kasuma Dewi; Hassan, Noorsilawati (2012)
This business is a partnership of 5 members. We consist of general manager, administration manager, operation manager, financial manager, and marketing manager. EMSA (Excellent Maid Service Agency) specialised in providing maid services in office and domestic cleaning. Our professional, friendly, and efficient maid are available for cleaning service on a one time, or ongoing basis for our clients' house, office, home or condo. We also provide intensive training for our helpers to ensure the efficacy in performing their duties. This company will be initiated on 2013. With dedication and commitment amongst partners, we believe we have great vision for a better tomorrow. Our mission is to be premier maid Service Company in Sabah. Operating in Kota Kinabalu, our group has chosen this company because most people that employed foreign maid face problems such as expensive application cost, long waits for foreign domestic helpers and painful adjustments problems. Now with EMSA, employing domestic helpers is just a phone call away. We increase our competitive advantages from other maid service agencies by providing room for development for the workers. We offer accommodation, transportation, and training for these workers. In an addition our package are reasonable and competitive for the service provided. This will help us to maintain our business and financial sustainability. With our competitive advantage and the increasing demand for local maid services, we expect our company will become one of Sabah's maid agency companies. We believe in carrying out standard service, and cater quality services for our clients. Hence, our slogan is "A Rotation towards Perfect Cleanliness".